REI: An integrated measure for software reusability. Issue 8 (22nd July 2019) - Zozas, Ioannis; Ampatzoglou, Apostolos; Bibi, Stamatia; Chatzigeorgiou, Alexander; Avgeriou, Paris; Stamelos, Ioannis
Abstract: To capitalize upon the benefits of software reuse, an efficient selection among candidate reusable assets should be performed in terms of functional fitness and adaptability. The reusability of assets is usually measured through reusability indices. However, these do not capture all facets of reusability, such as structural characteristics, external quality attributes, and documentation. In this paper, we propose a reusability index (REI) as a synthesis of various software metrics and evaluate its ability to quantify reuse, based on IEEE Standard on Software Metrics Validity. The proposed index is compared with existing ones through a case study on 80 reusable open‐source assets. To illustrate the applicability of the proposed index, we performed a pilot study, where real‐world reuse decisions have been compared with decisions imposed by the use of metrics (including REI). The results of the study suggest that the proposed index presents the highest predictive and discriminative power; it is the most consistent in ranking reusable assets and the most strongly correlated to their levels of reuse. The findings of the paper are discussed to understand the most important aspects in reusability assessment (interpretation of results), and interesting implications for research and practice are provided.